Negative Regulation and Protective Function of Natural Killer Cells in HIV Infection: Two Sides of a Coin - Sun, Yu; Zhou, Jie; Jiang, Yongjun (Frontiers in Immunology, 2022)
Natural killer (NK) cells are key components of the innate immune system and target tumors and virus-infected cells; however, NK cells do not impede the steps of human immunodeficiency virus (HIV) infection. NK cell functions are impaired and even negatively regulate other immune cell responses in HIV infection, although NK cells can kill HIV-infected cells and thus suppress HIV replication. Considerable recent research has emerged regarding NK cells in the areas of immune-senescence, immune checkpoints, negative regulation, and HIV reservoirs during HIV infection; however, it is lack of overall summary about them in HIV infection. This review focuses on several important aspects of the role of NK cells during HIV infection. For example, NK cells exhibit increased expression of immune checkpoint receptors and impaired cell functions. In addition, NK cells exhibit the features of immune-senescence and negatively regulate adaptive immune responses, but they still can play an antiviral role and even inhibit HIV reservoir formation. Chimeric antigen receptor (CAR)-NK cells exhibit specifically enhanced cell-killing activity, suggesting that CAR-NK cells could be employed to eliminate HIV reservoirs in the future.